Kedisiplinan Belajar Pesantren - Dalimunthe, Rasyid Anwar (Al-Fikru: Jurnal Ilmiah, 2019)
Discipline is an attempt to guide the improvement of behavior in accordance with the goals and ideals of education. In carrying out this guidance there are various educational actions such as, punishment, gifts, praise and sometimes something must be applied through force.The application of discipline to pesantren or other schools is not the same, both in terms of quality and quantity and frequency of implementation. The discipline of people who live in dipesantren is different from those who do not live in pesantren, especially students who study dipesantren. The essence of the discipline is to master the students' behavior directly by using penalties and prizes so that their achievements can improve in learning.The ultimate goal of the application of discipline in learning is the change in behavior and personal formation. If the application of discipline is successful in students themselves, then there has been an increase in learning achievement directly. Because the change in behavior referred to in learning covers the entire personality of the santri